Tap water as a wound cleansing agent in accident and emergency. - Riyat, M S (1997)
OBJECTIVE: To investigate the bacterial cleanliness of tap water in a large accident and emergency (A&E) department for its possible use in the cleansing and irrigation of open traumatic wounds. METHODS: Tap water samples were collected from different areas within the department and analysed on two separate occasions for coliforms, S aureus, clostridia, pseudomonas, and beta haemolytic streptococci. RESULTS: Pathogenic bacteria were not isolated from the tap water samples within the A&E department. CONCLUSIONS: Tap water of drinking quality can be used to irrigate open traumatic wounds.